Relationship Between Parents' Education and Income Level with Personal Hygiene Practices in Under-Five Children Care - Hasan, Nur Bilqis Haibah Mufidah; Witdiawati, Witdiawati; Kosim, Kosim; Rahayuwati, Laili; Yani, Desy Indra; Solehati, Tetti (Universitas Padjadjaran, 2024)
Poor personal hygiene practices can affect the incidence of infectious diseases which in turn can increase the risk of stunting. Several factors influence the practice of personal hygiene in the care of under-five children, namely the level of education and income of parents. The research was to analyze the relationship between parents' education and income level with personal hygiene practices in under-five children's care. The research design is a quantitative correlation with secondary data sources. The population is parents who have under-five children in Sukamulya Village, Bandung. Samples were taken using an accidental sampling technique with a total of 85 respondents, excluding parents whose children died in the under-five age range or whose children were 5 years old at the time of data collection. The instrument is a questionnaire consisting of demographic data and 7 questions related to personal hygiene practices in caring for under-five children. The data were analyzed using the Spearman test. The results showed that there was no relationship between the educational (p-value=0.16) and income (p-value=0.887) level of parents with personal hygiene practices in caring for under-five children in Sukamulya Village, Bandung. The next research suggestion is to examine other factors that influence personal hygiene practices in caring for under-five children.